Protective effects of 5, 7, 4′-trihydroxy-6, 3′dimethoxy-flavone 5-O-α-l-rhamnopyranoside, isolated from Annona squamosa leaves in thyrotoxicosis and in hepatic lipid peroxidation in rats. Issue 24 (15th December 2015) - Panda, Sunanda; Kar, Anand
Graphical abstract: Abstract: Hitherto unknown protective effects of 5, 7, 4′-trihydroxy-6, 3′dimethoxy-flavone 5- O -α-l -rhamnopyranoside (THDMF-Rha); isolated from Annona squamosa leaves were evaluated inl -thyroxine (l -T4 )-induced thyrotoxicosis in rats. Administration ofl -T4 at 500 μg/kg body weight for 12 days increased the levels of serum thyroid hormones, the activity of 5′-monodeiodinase-I (5′DI) and hepatic glucose-6-phosphatase (G-6Pase) as well as lipid peroxidation (LPO); with a parallel decrease in the levels of cellular antioxidants and serum lipids. However, administration of the isolated THDMF-Rha at a pre-standardized dose for 15 days ameliorated thel -T4 -induced alterations in the levels of thyroid hormones, hepatic LPO, G-6-Pase, 5′DI activity, and cellular levels of antioxidants and improved the status of different serum lipids, suggesting its antithyroidal and antioxidative potential. As compared to standard antithyroid drug, propylthiouracil, THDMF-Rha appeared to be more promising.